Optimalisasi Fintecht Peer to Peer Lending dalam Hukum Ekonomi Syariah Untuk Mewujudkan Maqashid Syariah - Widyasputri, Viesta Tya Amanda; Baidhowi (Universitas Negeri Semarang, 2025)
Sharia-based Fintech Peer-to-Peer (P2P) Lending is developing as a digital financial innovation that aims to increase financial inclusion in accordance with Islamic principles. This research aims to analyze the regulation of Fintech P2P Lending in sharia economic law, evaluate the implementation of sharia contracts, and assess its contribution in realizing Maqashid Syariah. This research uses a normative juridical method with a literature study approach that refers to regulations, Fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and related literature. The results showed that the regulation of sharia Fintech P2P Lending still needs strengthening, especially in the aspects of legal certainty and supervision. The implementation of sharia contracts such as Murabahah and Musyarakah has been implemented, but still faces challenges of transparency and propriety. Fintech P2P Lending has the potential to support Maqashid Syariah, especially in fair financial distribution and consumer protection. Regulatory optimization and sharia contract innovation are needed so that Fintech P2P Lending can further contribute to the sharia-based financial system